Green synthesis and characterization of gold nanoparticles using pomegranate peel extract for inhibition of calcium oxalate crystals and uropathogenic bacteria - Mundhewadikar, Dhananjay M.; Bhalerao, Minal R.; Vairale, Shiva; Sabir, Safiya; Mote, Chandrashekhar; Chowdhury, Chiranjit; Agawane, Sachin B. (BioNanoScience, 2025)
This study explores the therapeutic potential of pomegranate peel extract (PPE) and its gold nanoparticle conjugate (PPE-AuNP) in the prevention and treatment of urolithiasis. Pomegranate peels collected from four agro-climatic zones of India exhibited consistent methanolic extract yields (10–17%) and total phenolic content, with the highest levels observed in the West zone. Green synthesis of PPE-AuNPs was confirmed through UV–Vis spectroscopy (λmax = 522 nm), DLS (38.2 ± 2.1 nm), zeta potential (-33.66 ± 2.97 mV), and TEM imaging, which showed uniform spherical nanoparticles. Characterization confirmed that PPE-AuNPs were crystalline and phytochemically capped. FTIR shifts in O–H, C = O, and C–O bands, along with a ~ 500 cm-1 Au–O/N vibration, confirmed phytochemical-mediated reduction and stabilization. XRD revealed an FCC structure with a dominant (111) plane, indicating high crystallinity. The synthesized nanoparticles demonstrated antioxidant activity with an IC50 of 21.53 µg/mL, superior to PPE and AuNP alone. In vitro calcium oxalate crystallization assays revealed significant crystal inhibition by PPE-AuNPs, confirmed via E-SEM, EDAX, and XRD analyses. Antibacterial studies against E. coli, K. pneumoniae, S. aureus, and uropathogenic E. coli showed MIC values of 31.25–62.5 µg/mL for PPE and PPE-AuNPs, with negligible activity from AuNP alone. In vivo studies in ethylene glycol-induced urolithiatic rats revealed significant improvement in urinary parameters, renal biochemistry (creatinine, urea, SGPT, SGOT), hematological markers, and histopathology, especially in the PPE-AuNP-treated group. PPE-AuNP treatment normalized urinary appearance, reduced serum creatinine and blood urea nitrogen (BUN), and restored renal architecture with minimal degeneration. The enhanced therapeutic effects of PPE-AuNPs are attributed to their bioactive phenolic surface ligands and colloidal stability. Overall, this study demonstrates the synergistic efficacy of PPE-AuNPs as a potent, green nanotherapeutic agent for urolithiasis, offering antioxidant, antibacterial, and nephroprotective effects with promising translational relevance.

Novel prodrug-inspired eugenol derivatives with enhanced bioavailability, anti-diabetic and anti-glycation efficacies - Kataria, Priyanka; Vairale, Shiva; Mote, Chandrashekhar; Joshi, Kaustubh; Joshi, Rakesh; Kulkarni, Mahesh J.; Giri, Ashok P.; Kontham, Ravindar; Agawane, Sachin B. (Journal of Molecular Structure, 2026)
In this study, we present the design, synthesis, and evaluation of novel eugenol analogs aimed to overcome its limited bioavailability due to insolubility in aqueous media. Thus, we re-engineered eugenol using prodruginspired structural modifications to improve pharmacokinetic properties. First, we structurally modified eugenol and synthesized its natural amino acid conjugates as esters and carbamates. These were prepared in NBoc protected, free amine, and HCl salt forms. These modifications are expected to improve the polarity and solubility of eugenol congeners in biological systems. They can also release the parent eugenol through enzymatic hydrolysis, enhancing its therapeutic potential. Next, we comprehensively screened for these derivatives through in silico studies followed by in vitro and in vivo assays. These include DPPH radical scavenging (IC50 range: 37.7 to 103.7 mu M), inhibition of (i) alpha-amylase (IC50 23.1 to 67.3 mu M), (ii) alpha-glucosidase (IC50 43.6 to 50.4 mu M), (iii) glycation (IC50 31.9 to 110.3 mu M) along with pharmacokinetic profiling and toxicity assessments. These experiments collectively demonstrated improved activity of eugenol analogs for several important parameters. Specifically, six analogs-epoxy eugenol (39), hydroxy eugenol (43), aspartate eugenol (26), isoleucinate eugenol (24), glutamate eugenol (37), and glutamate-salt eugenol (27) exhibited superior bioavailability, absorption, and distribution over to the parent compound eugenol. These analogs were found to be non-toxic and safe for oral administration. Overall, the study establishes a mechanistic and rational framework for modifying eugenol to overcome its inherent biopharmaceutical limitations, positioning them as promising candidates for treating diabetes and glycation-related conditions.
Keywords: Amino acid conjugates; Antidiabetic activity; Bioavailability enhancement; Drug design and synthesis; Eugenol analogs; In silico and in vitro studies